Impaired cerebral oxygenation in heart failure patients at rest and during head‐up tilt testing. (9th December 2020) - Kharraziha, Isabella; Holm, Hannes; Magnusson, Martin; Wollmer, Per; Molvin, John; Jujic, Amra; Fedorowski, Artur; Bachus, Erasmus; Hamrefors, Viktor
Abstract: Aims: Heart failure (HF) confers potentially negative effects on the brain and autonomic nervous system. The measurement cerebral tissue oxygen saturation (SctO2 ) may aid in understanding such effects. We aimed to investigate if compensated HF affects SctO2 at rest and during orthostatic challenge. Methods and results: Non‐invasive haemodynamic monitoring and near‐infrared spectroscopy were applied during head‐up tilt (HUT) in 61 HF patients [mean (SD) 71 (11) years, 82% male, New York Heart Association (NYHA) class I–III] and 60 controls [60 (12) years, 42% male). Group differences in continuous variables were compared using Student's t ‐test. Associations between HF and SctO2 were studied using multivariable linear regression models adjusted for age, sex, diabetes, smoking, systolic blood pressure (SBP), and heart rate in supine position and after 10 min of HUT. Mean SctO2 was lower in HF patients compared with controls both in the supine position (67 vs. 71%; P  < 0.001) and after 10 min of HUT (64 vs. 69%; P  < 0.001). The HUT‐induced SctO2 decrease was greater in HF patients compared with controls ( P  = 0.026). SBP did not change in neither HF patients nor controls during HUT, whereas diastolic blood pressure and heart rate increased in both groups. HF was associated with lower SctO2 in supine ( B  = −2.5%, P  = 0.023) and after 10 min of HUT ( B  = −2.6%, P  = 0.007) after multivariable adjustments. Conclusions: Cerebral tissue oxygenation is lower in HF patients both at rest and during orthostasis compared with subjects without HF. Future studies should test if the lower cerebral oxygenation associates with negative prognosis and with impaired cognitive function.